Industrial training report: Hospital Tanah Merah (Kelantan) / Farhah Mohammad Nasir - Mohammad Nasir, Farhah (Perpustakaan Tengku Anis, 2017)
This industrial training report consists of 4 chapters and that are introduction organization of information, industrial training activities and conclusion. Chapter 1 consists of background of the organization, chapter 2 consists of departmental structure and function. While chapter 3 consist of training activities and special project and the last chapter is chapter 4 which has the conclusion of the report. In order to complete study, trainee needs to undergo five months of practical training in Industry starting from 1st February 2017 until 31st June 2017. The placement that has been choose by the trainee is ICT Unit in Hospital Tanah Merah. During five months of training, the trainee got opportunity to learn IT field in ICT Unit. Trainee scheduled has been prepared by the supervisor of practical training for the trainee to learn important task at ICT Unit, Besides that, student also learn to improve communication skills, learn to be more discipline and punctual. Last but not least, the knowledge, skills and experience gain during the practical training is the best method I order to prepare student to expose to the real working environment and also to be a good and better worker in future.